Crime victims in the criminal justice system - Ćopić Sanja M. (Temida)
Negative social reaction and inadequate reaction of the agencies of the formal control on the primary victimization is leading to the so called secondary victimization that can be a source of trauma and frustration as much as the primary victimization. Due to that, relation of the police and the judiciary towards the crime victims is of a great importance regarding victims’ willingness to report the victimization, their confidence in these agencies, and cooperation during clearing up the crime. In order to realize the victim’s position in the criminal justice system, this paper contains an overview of how the police, prosecutor’s office and courts are functioning. The paper is based on the interviews made with the representatives of these state agencies, as well as on the previous knowledge and realized surveys concerning this topic. The aim of the paper is to emphasize the position and the role of the victim support service in the system of the state intervention, based upon the obtained data, as well as to give some basic information on how victims could report the crime, what are their rights and duties, what can they expect from the competent agencies.